Fatigue-Based Structural Layer Coefficient of High Polymer-Modified Asphalt Mixtures. Issue 3 (March 2020) - Habbouche, Jhony; Hajj, Elie Y.; Sebaaly, Peter E.; Hand, Adam J.
Florida Department of Transportation uses the 1993 AASHTO guide to conduct new and rehabilitation designs for all the state's flexible pavements. Based on previous experience, a structural layer coefficient of 0.44 was found to be well representative of the department's conventional polymer-modified (PMA) asphalt concrete (AC) mixtures. If the positive impact of the polymer on the layer is assumed to be maintained at higher contents, then the use of high polymer-modified (HP) asphalt binder may lead to a higher AC structural layer coefficient and a reduced AC layer thickness for the same design traffic and serviceability design loss. The objective of this paper was to determine a fatigue-based structural layer coefficient for asphalt mixtures that contain HP binder using comprehensive mechanistic analyses. This approach relied on combining measured engineering properties and performance characteristics of AC mixtures with advanced flexible pavement modeling (3D-Move). A total of eight PMA and eight HP AC mixtures were designed and evaluated in the laboratory. Overall, the HP AC mixtures showed similar or lower dynamic modulus and better fatigue performance models when compared with those of their respective PMA AC mixtures. However, the fatigue-based structural layer coefficients, determined via mechanistic analysis using the service life approach, ranged between 0.33 (lower than 0.44) and 1.32 (greater than 0.44). Using advanced statistical analyses, a fatigue-based structural layer coefficient of 0.54 was determined for HP AC mixtures. This coefficient should still be verified for other modes of distress.